Decisional enhancement and autonomy: public attitudes towards overt and covert nudges - Gidon Felsen; Noah Castelo; Peter B. Reiner (Judgment and Decision Making, 2013)
Ubiquitous cognitive biases hinder optimal decision making. Recent calls to assist decision makers in mitigating these biases---via interventions commonly called ``nudges''---have been criticized as infringing upon individual autonomy. We tested the hypothesis that such ``decisional enhancement'' programs that target overt decision making---i.e., conscious, higher-order cognitive processes---would be more acceptable than similar programs that affect covert decision making---i.e., subconscious, lower-order processes. We presented respondents with vignettes in which they chose between an option that included a decisional enhancement program and a neutral option. In order to assess preferences for overt or covert decisional enhancement, we used the contrastive vignette technique in which different groups of respondents were presented with one of a pair of vignettes that targeted either conscious or subconscious processes. Other than the nature of the decisional enhancement, the vignettes were identical, allowing us to isolate the influence of the type of decisional enhancement on preferences. Overall, we found support for the hypothesis that people prefer conscious decisional enhancement. Further, respondents who perceived the influence of the program as more conscious than subconscious reported that their decisions under the program would be more ``authentic''. However, this relative favorability was somewhat contingent upon context. We discuss our results with respect to the implementation and ethics of decisional enhancement.